In vitro reduction of enamel erosion by sugarcane-derived cystatin associated with sodium trimetaphosphate - Ferrari, Carolina Ruis; Kitamoto, Karolyne Sayuri de Araujo; PELÁ, Vinicius Taioqui; Taira, Éven Akemi; ARAÚJO, Tamara Teodoro; Thomassian, Larissa Tercilia Grizzo; HENRIQUE-SILVA, Flávio; Pessan, Juliano Pelim [UNESP]; Buzalaf, Marília Afonso Rabelo (FapUNIFESP (SciELO), 2024)
The objective of this in vitro study was to assess the efficacy of CaneCPI-5, either alone or in combination with various concentrations of sodium trimetaphosphate (TMP) in protecting against initial enamel erosion. A total of 135 bovine enamel specimens were prepared and categorized into nine groups (n/group=15) according to the following treatments: Deionized water; Commercial solution (Elmex Erosion ProtectionTM); 0.1 mg/mL CaneCPI-5; 0.5% TMP; 1.0% TMP; 3.0% TMP; 0.1 mg/mL CaneCPI-5+0.5% TMP; 0.1 mg/mL CaneCPI-5+1.0%TMP; and 0.1 mg/mL CaneCPI-5+3.0%TMP. The specimens were treated with the respective solutions for 2 h, followed by acquired enamel pellicle formation for 2 h and exposure to 0.65% citric acid (CA) for 1 min. These procedures were repeated once a day for three consecutive days. Demineralization was assessed by the percentage change in surface hardness (%CSH) and calcium release into CA, analyzed by the Arsenazo III method. The data were evaluated using Kruskal-Wallis/Dunn's tests. Regarding %CSH, CaneCPI-5+3.0%TMP was the most effective treatment when compared to the CaneCPI-5 group alone. As for calcium release into CA, the CaneCPI-5+0.5% TMP and CaneCPI-5 groups (both with lower calcium release) did not significantly differ from the commercial solution. In conclusion, combination of CaneCPI-5 with TMP enhances the protective potential against initial enamel erosion in vitro.
Keywords: Cystatins; Dental Pellicle; Saliva; Tooth Erosion